The effect of increasing retirement age on consumption in China. (4th August 2021) - Cao, Zhan; Tang, Yizhou
Abstract : This paper discusses a factor influencing consumption in China that has not been widely addressed: the retirement age. Many previous studies on the relationship between retirement age and consumption are based on data from developed countries. Because of the many differences between China and the developed economies, this analysis relies on the Lau (2009) overlapping‐generations model. This model is more suitable for determining the relationship between consumption and retirement age in China, and for highlighting the positive relationship between consumption and retirement age. The empirical results reveal a causal relationship between retirement age and consumption and indicate that increasing the retirement age can stimulate economic growth. These results are specific to China and include gender differences and the varied impacts on low‐income and high‐income families.